Comparative study of bronchoalveolar lavage, bronchial brushing, and FNAC in diagnosing malignant neoplasms of lungs - Tomar, Vijeta (J Cytol, 2016)
BACKGROUND: Lung cancer is the leading cause of death in developed countries and is increasing at alarming rates in developing countries. Cytological techniques such as bronchoalveolar lavage (BAL), bronchial brushing (BB), and fine needle aspiration cytology (FNAC) can aid in the early diagnosis of lung malignancies. MATERIALS AND METHODS: A total of 67 cases, suspected of lung cancer between January 2010 and December 2012, were selected where samples of BAL, BB, FNAC, as well as biopsy were obtained and processed according to the standard procedures of cytology and histology. The aim of this study was to compare the diagnostic efficacy of the three modalities, i.e., BAL, BB, and FNAC in diagnosing malignant neoplasms of the lung. Biopsy was considered to be the gold standard diagnostic test. RESULTS: Sensitivity of BAL, BB, and FNAC was found to be 47.61, 65.07, and 88.88%, respectively, whereas specificity of BAL, BB, and FNAC was 75, 75, and 100%, respectively. CONCLUSIONS: FNAC is the best technique among the three for the diagnosis of lung cancers.